Literasi alam sekitar menurut paradigma agama - Rozita Ibrahim, (Universiti Kebangsaan Malaysia, 2002)
Environmental literacy refers to the specific literacy that promotes responsible environmental behavior. Theoretically speaking, environmental literacy operates in a continuum, beginning with awareness and concern of an issue, understanding of the issue and finally taking appropriate action. Since the term was introduced, the distinguishing character has been its ‘action’ perspective, which refers to the highest level of the continuum i.e. operational environmental literacy. This is crucial since the true indicator of environmental commitment is the action taken by individuals, community and society. This paper will discuss the concept of environmental literacy and its relevance in contemporary society. The author argues that a promising way in promoting environmental literacy is through the understanding of values and ethics with regard to the relationship of man and his environment within Islamic paradigm